Kampung Naga Community Education Development Pattern: Traditional Sociology Overview - Eni Setyowati (HK-Publishing, 2022)
AbstractKampung Naga is one of the traditional villages or cultural villages in Indonesia, besides the kampung naga there are still many other cultural villages in Indonesia. However, this dragon village has an open society to global developments or the times. This can be seen in various aspects, namely the aspect of education where the children of the Naga village community are given the freedom to study outside the village or even outside the city. The thinking of the Kampung Naga community is very broad in thinking about the ideals and hopes of their children to be successful with the abilities and education they get in this formal education. In this study, the aim of this research is to find out how education plays an important role for the community of the Kampung Naga, and how the development of the Kampung Naga community from the aspects of education, health, livelihood and technology. The methods used are qualitative methods and literature. After making observations with various sources and coming to the location directly, the researchers get the results that the role of education is important for the people of the Kampung Naga to arrange a better life in the future for their children.Keywords: Education, Development, Kampung Naga Community AbstrakKampung Naga merupakan salah satu kampung adat atau kampung budaya yang ada di Indonesia, selain kampung naga masih banyak kampung budaya lainnya di Indonesia. Namun, desa naga ini memiliki masyarakat yang terbuka terhadap perkembangan atau perkembangan global. Hal ini terlihat dalam berbagai aspek yaitu aspek pendidikan dimana anak-anak masyarakat desa Naga diberikan kebebasan untuk belajar di luar desa atau bahkan di luar kota. Pemikiran masyarakat Kampung Naga sangat luas dalam memikirkan cita-cita dan harapan anak-anaknya agar sukses dengan kemampuan dan pendidikan yang mereka dapatkan di pendidikan formal ini. Dalam penelitian ini, tujuan dari penelitian ini adalah untuk mengetahui bagaimana pendidikan berperan penting bagi masyarakat Kampung Naga, dan bagaimana perkembangan masyarakat Kampung Naga dari aspek pendidikan, kesehatan, mata pencaharian dan teknologi. Metode yang digunakan adalah metode kualitatif dan kepustakaan. Setelah melakukan observasi dengan berbagai sumber dan datang ke lokasi secara langsung, peneliti mendapatkan hasil bahwa peran pendidikan penting bagi masyarakat Kampung Naga untuk menata kehidupan yang lebih baik di masa depan bagi anak-anaknya.Kata kunci: Pendidikan, Pengembangan, Komunitas Kampung Naga